Economic Performance Of Manufacturing Companies In Indonesia: Long Term Debt, Pre-Tax Foreign Income And Earning Management - Damayanty, Prisila; Prihanto, Hendi; Mulyadi, Mulyadi; Ulan Sari, Riski (International Journal of Educational Research & Social Sciences, 2022)
[1] Al-tuwaijri, S. A., Christensen, T. E., & Ii, K. E. H. (2004). The relations among environmental disclosure , environmental performance , and economic performance : a simultaneous equations approach. 29, 447–471. https://doi.org/10.1016/S0361-3682(03) 00032-1.[2] Almilia, L. S., & Wijayanto, D. (2007). The Effect of Environmental Performance on Environmental Disclosure and Economic Performance. Proceedings The 1st Accounting Conference, (November), 7–9. https://doi.org/10.21002/jaki.2012.04[3] Anton, F. (2010). Towards the Theory of Stewardship management. Scientific Magazine of Informatics, 1(2), 61–80.[4] Arista, D. (2012). Factor Analysis - Factors Affecting Stock Returns (The Case of Manufacturing Companies That Went Public on the IDX for the Period of 2005 - 2009). Journal of Applied Management And Accounting Sciences, 3, 1–15.[5] Benny, J. (2013). Exports and Imports Affect the Position of Foreign Exchange Reserves in Indonesia. Emba Journal. ISSN : 2303-1174, 1(4), 1–10. Retrieved froM http://ejournal.unsrat.ac.id/index.php/emba/article/view/2920/2471[6] Damayanti, E., Laksono, P., Rini, I., & Pangestuti, D. (2018). Company Debt and Profitability (Study on Real Estate and Property Companies Listed on the Indonesia Stock Exchange). 7(2012), 2012–2018.[7] Dewata, B. K., & Swara, I. W. Y. (2013). The Effect of Total Exports, Libor, and Labor Wages on Foreign Direct Investment in Indonesia. E-Journal of Development Economics, Udayana University, 2, 350–358.1575International Journal of Educational Research & Social Sciences ISSN: 2774-5406https://ijersc.org[8] Dewi, L. K., Putu, D., & Sukartha, Y. (2015). The Relationship between Financial Performance and Return Corporate Social Responsibilty is investing. In the current era of globalization, investors are increasingly required to be used as a source of analysis of fundamental factors of companies. 3, 516–529.[9] Donaldson, L., & Davis, J. H. (1991). Stewardship Theory or Agency Theory: CEO Governance and Shareholder Returns. Australian Journal of Management, 16(1), 49–64. https://doi.org/10.1177/031289629101600103[10] Eksandy. (2018). Accounting and Management Research Methods[11] Fernando, N. (2017). Analysis of Economic Performance of Manufacturing Companies in Indonesia. 9(2), 132–142.[12] Higgins, D., Omer, T. C., & Phillips, J. D. (2011). The Influence of a Firm's Business Strategy on its Tax Aggressiveness. Ssrn, XX(Xx), 1–29. https://doi.org/10.2139/ssrn.1727592[13] INDEF. (2017). Towards Indonesia's Economic Resilience: Contributing suggestions to 100 Indonesian Economists.[14] Mada, U. G., Setiawati, L., & Na'im, A. (2000). Profit Management, 15(4), 424–441.[15] Priyanto, S., & Darmawan, A. (2017). Effect of Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Long Term Debt to Asset Ratio (LDAR) and Long Term Debt to Equity Ratio (LDER) on Profitability (ROE) on Manufacturing Companies on the Indonesia Stock Exchange for the 2012-2014 Period. Journal of Economic Media Management and Business, XVII(1), 25–32.[16] Raharjo, E. (2007). Agency Theory And Stewarship Theory In Accounting Perspective. Economic Focus : Scientific Journal of Economics, 2(1), 27–46. https://doi.org/10.34152/FE.2.1.%P[17] Rizky, R. L., Agustin, G., & Mukhlis, I. (2016). The Effect of Foreign Investment, Domestic Investment and Capital Expenditure on Provincial Economic Growth in Indonesia. Journal of Economics and Economics of Development Studies, 8(1), 9–16. https://doi.org/10.17977/um002v8i12016p009[18] Shopia, A., & Sulasmiyati, S. (2018). The Effect of Foreign Direct Investment, Exports, and External Debt on ASEAN Economic Growth (Study on gross domestic product of Indonesia, Malaysia, and Thailand for the period 2007 - 2016). Journal of Business Administration (JAB), 61(3), 20–28. Retrieved from administrasibisnis.studentjournal.ub.ac.id%0A20[19] Stubben, S. (2010). Discretionary Revenues as a Measure of Earnings Management Working Paper. 85(2), 695–717.[20] Tristianasari, G. (2014). Economic Performance Analysis of the Company. 3(2), 135–146.[21] Wibowo, S. (2016). The effect of debt to equity ratio, debt ratio, long term debt, long term debt to equity ratio, and liquidity on profitability in pharmaceutical companies. 8(1), 22–28.